Reference Clinical Database for Fixation Stability Metrics in Normal Subjects Measured with the MAIA Microperimeter - Morales, Marco U.; Saker, Saker; Wilde, Craig; Pellizzari, Carlo; Pallikaris, Aristophanes; Notaroberto, Neil; Rubinstein, Martin; Rui, Chiara; Limoli, Paolo; Smolek, Michael K.; Amoaku, Winfried M. (Translational vision science & technology, 2016)
The purpose of this study was to establish a normal reference database for fixation stability measured with the bivariate contour ellipse area (BCEA) in the Macular Integrity Assessment (MAIA) microperimeter. Subjects were 358 healthy volunteers who had the MAIA examination. Fixation stability was assessed using two BCEA fixation indices (63% and 95% proportional values) and the percentage of fixation points within 1° and 2° from the fovea (P1 and P2). Statistical analysis was performed with linear regression and Pearson's product moment correlation coefficient. Average areas of 0.80 deg (min = 0.03, max = 3.90, SD = 0.68) for the index BCEA@63% and 2.40 deg (min = 0.20, max = 11.70, SD = 2.04) for the index BCEA@95% were found. The average values of P1 and P2 were 95% (min = 76, max = 100, SD = 5.31) and 99% (min = 91, max = 100, SD = 1.42), respectively. The Pearson's product moment test showed an almost perfect correlation index, = 0.999, between BCEA@63% and BCEA@95%. Index P1 showed a very strong correlation with BCEA@63%, = -0.924, as well as with BCEA@95%, = -0.925. Index P2 demonstrated a slightly lower correlation with both BCEA@63% and BCEA@95%, = -0.874 and -0.875, respectively. The single parameter of the BCEA@95% may be taken as accurately reporting fixation stability and serves as a reference database of normal subjects with a cutoff area of 2.40 ± 2.04 deg in MAIA microperimeter. Fixation stability can be measured with different indices. This study originates reference fixation values for the MAIA using a single fixation index.